Irrigation and agricultural transformation in Ethiopia - Mekonnen, Dawit Kelemework; Abate, Gashaw T.; Yimam, Seid (International Food Policy Research Institute, 2022)
Ethiopia’s rivers and streams (Figure 1) and its ground water potential of 2.6 billion m3 of groundwater potential (Awulachew et al., 2008) is estimated to have a potential to irrigate 5.3 million hectares of land. So far, less than 5 percent of the potentially irrigable land is currently irrigated, exposing the country’s agriculture to the vagaries of nature. The startling divergence between irrigation potential and utilization has been the subject of policy discussions in the recent decade, which results in a significant impetus towards irrigation development in the country both in expressed commitments and actual investments. For instance, the current 10-year development plan of the country placed irrigation as the main catalyst for accelerated agricultural transformation. In terms of investment, there are at least 13 ongoing large-scale irrigation development projects with a combined command area of more than 400,000 hectares (close to twice the current size of irrigated area by smallholder farmers). The government has also recently allowed duty-free imports of irrigation technologies to encourage small-scale irrigation development.